Destination resilience and transformations in the tourism sector: new tendencies in destination development and management - Sahil Sharma; Jeet Dogra; Sonia Khan (Tourism & Management Studies)
The world is increasingly changing, with climate change, pandemics, and wars becoming key factors. The recent pandemic devastated the tourism industry, leading to a sudden collapse of the global tourism economy. Historically disastrous situations are well known for their impact on innovations and technological advances. Therefore, in light of the idea that disasters can act as catalyst for innovation and transformation, the researchers attempted to conceptualise new strategies in destination development and management from a perspective of tourism destination resilience. The findings contribute to research and policy-making and culminate in identifying six dimensions, namely technology and digitalisation, business model innovation, partnerships and coordination, tourist behaviour, domestic tourism, and sustainability, that illuminate innovative and transformative tendencies in tourism resilience. The study's outcomes offer comprehensive knowledge for policymakers, business planners, and students describing the use of innovative ideas and resilience strategies to adapt to and counter sudden disasters and adopt transformational shifts in business.